Physicochemical Characteristics of Beef Meatballs at Various Post Mortem Phases with the Addition of Seaweed Flour (Gracillaria sp.) - Wahyuningtyas, Ririh; Yulistiani, Ratna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The post-mortem phase of meat influences the physicochemical quality of the beef meatballs produced. The post mortem phase is the phase that meat goes through after slaughter. The post mortem phase is divided into 3, namely prerigor, rigor mortis and post rigor. Seaweed (Gracillaria sp.) can be used as a natural chewy meatball. This research aims to determine the best treatment combination between the post-mortem phase of meat and the addition of seaweed flour on the physicochemical characteristics and preferences of beef meatballs. This research used a completely randomized design with a factorial pattern with 2 factors with two replications. Factor I is the post mortem phase (pre-rigor, rigormortis and post-rigo). Factor II is the addition of seaweed flour (3%, 4% and 5%). The observation data were analyzed using ANOVA, if there were significant differences, the Duncan Multiple Range Test was carried out at the 5% level. The best treatment results were pre-rigor beef treatment with the addition of 5% seaweed flour, producing meatballs with characteristics of 69.05% water content, 2.93% ash content, 1.55% fat, 12.49% protein, 12.92N elasticity level, 47.22% water holding capacity. , Color preference level 4 (like really), aroma 4.07 (like really), taste 4.17 (like really) and texture 4.50 (like really).